Lateral Preoptic Area Neurons Activated by Angiotensin-(1–7) Increase Intravesical Pressure: A Novel Feature in Central Micturition Control - Lamy, Gustavo B.; Cafarchio, Eduardo M.; do Vale, Bárbara; Antonio, Bruno B.; Venancio, Daniel P.; de Souza, Janaina S.; Maciel, Rui M.; Giannocco, Gisele; Aronsson, Patrik; Sato, Monica A. (Frontiers in Physiology, 2021)
Central micturition control and urine storage involves a multisynaptic neuronal circuit for the efferent control of the urinary bladder. Electrical stimulation of the LPA at the level of the decussation of the anterior commissure in cats evokes relaxation of the bladder, whereas ventral stimulation of LPA evokes vigorous contraction. Endogenous Angiotensin-(1-7) [(Ang-(1-7)] synthesis depends on ACE-2, and its actions on binding to Mas receptors, which were found in LPA neurons. We aimed to investigate the Ang-(1-7) actions into the LPA on intravesical pressure (IP) and cardiovascular parameters. The gene and protein expressions of Mas receptors and ACE-2 were also evaluated in the LPA. Angiotensin-(1-7) (5 nmol/µL) or A-779 (Mas receptor antagonist, 50 nmol/µL) was injected into the LPA in anesthetized female Wistar rats and the IP, mean arterial pressure (MAP), heart rate (HR) and renal conductance (RC) were recorded for 30 min. Unilateral injection of Ang-(1-7) into the LPA increased IP (187.46±37.23%) with peak response at ~23-25 min post-injection and yielded no changes in MAP, HR and RC. Unilateral or bilateral injections of A-779 into the LPA decreased IP (-15.88 ± 2.76 and -27.30±3.40%, respectively) and elicited no changes in MAP, HR and RC. The genes and the protein expression of Mas receptors and ACE-2 were found in the LPA. Therefore, the LPA is an important part of the circuit involved in the urinary bladder control, in which the Ang-(1-7) synthetized into the LPA activates Mas receptors for increasing the IP independent on changes in RC and cardiovascular parameters.